DIMENSI METRIK PADA GRAF HASIL KALI SISIR PADA GRAF LINTASAN TERHADAP BEBERAPA GRAF REGULER - Padoma, Widya Aprilia; Gafur, Anuwar Kadir Abdul (Universitas Pasifik Morotai, 2025)
Let be a graphs finite, simple, and connected. A set of vertices subset of . For , a representation of with respect to is defined as -tuple . The set is a resolving set of if ever two distinct vertices satisfy A basis of is a resolving set of with minimum cardinality, and the metric dimension of refers to its cardinality, denoted by . In this research, Suhadi W Saputro et al have found the metric dimension of the comb product graph if leaf or jika not a leaf. Therefore, we will be looking for the metric dimension of the product of a comb on a path graph to some regular graph and we have managed to find if the copy vertices of . For , let is a path end is -regular or is -regular. Then for or for